Impact of “Nepal Tourism Year 2011” on Tourist Arrival in Pokhara - Parajuli, Biswo Kallyan; Paudel, Yog Raj (Himalayan Journal of Sociology and Anthropology, 2014)
Tourism is a growing industry in Nepal. Pokhara is one of the major tourist destinations in Nepal. To foster the tourism industry in Nepal then government of Nepal decided on 2008 to launch a national tourism campaign “Nepal Tourism Year 2011” targeting to bring one million international tourists into Nepal in the year 2011. This paper focuses on analyzing the impact of Nepal Tourism Year 2011’s advertisement campaign on tourist arrival in Pokhara city. Also it attempts to highlight the impact of network and information access on tourism arrival. A sincere attempt has also been made to investigate the impact of NTY in bringing international tourist in Nepal particularly in Pokhara. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10687 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 22-50